Simeon Martin mit Frau und Kind in Okak 1912 - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of Simeon Martin with his wife and children sitting on a sled at Okak in 1912. He is wearing a pair of snow goggles. Photograph of Simeon Martin with his wife and children sitting on a sled at Okak in 1912. He is wearing a pair of snow goggles.